Food Security in Africa's Secondary cities : no. 1. Mzuzu, Malawi - Riley, Liam; Joynt, Amanda, 1977-; Zuze, Lovemore; Chilanga, Emmanuel (Urban food security series ;, 2018)
This report marks the first stage of AFSUN's goal of expanding knowledge about urban food systems and experiences of household food insecurity in secondary African cities. It contributes to an understanding of poverty and sustainability in Mzuzu, Malawi, through the lens of household food security. The focus on food as an urban issue not only speaks to the development challenges presented by urbanization, but it also brings a fresh perspective to debates about food security in Malawi. The urban setting highlights the changing food system in Malawi where people in rural and urban areas are increasingly reliant on cash income to buy food. The report's key findings include that the most vulnerable households are those without a formal wage income, households headed by older people, especially older women, and households that are not able to produce food in the rural areas. The research also shows that the food system is dynamic and diverse, with households accessing food from a variety of formal and informal food sources and relying on rural-urban linkages for urban survival. Urban and rural agriculture are important features of the food system, but there is little evidence that these are the "self-help" responses to poverty that advocates for urban agriculture in Africa sometimes imply.